Sistem Monitoring Prestasi Akademik Siswa Pada Sekolah Menengah Atas Negeri 5 Pagar Alam - Asep Syaputra (Department of Science and Technology Ibrahimy University, 2020)
The process of monitoring academic activity of SMA N 5 Pagar Alam City is still manual, because the data storage is still scattered in each field of teachers, sometimes the data entered in Microsoft Excel is not very accurate. From this problem, then a system of monitoring the processing of academic achievement data to determine the academic achievement of each student, where achievement data in the form of scores and activities of extracurricular activities will be easier to process, and the creation of reporting will be easier. This research uses waterfall methods and UML design, the devices used to build these systems using PHP and MySQL programming as databases. The system can be applied as a monitoring of students' academic performance so that academic data can be stored properly. The result of this study is the system of monitoring the academic achievement of high school students N 5 Pagar Alam City, with this system the school and parents are more effective in controlling and assessing activities related to the academic achievement of students.